Pengaruh Tingkat Pendidikan Dewan Direksi, Pertumbuhan Perusahaan, Profitabilitas, dan Umur Perusahaan Terhadap Manajemen Laba - Putri, Tia Kartika; Martias, Dony (Basecamp Economics PubMed, 2024)
This research is a quantitative study which aims to determine the influence of education board level, company growth, profitability and company age on earnings management in transportation and logistics sector companies listed on the Indonesia Stock Exchange (BEI) year period 2020-2022. In determining the research sample, a purposive sampling technique was used with a total population 50 companies and samples total 19 companies. This research uses secondary data obtained from company financial report data. The data analysis technique uses panel data regression analysis (pooled data) with the help of the program Eviews 12. The results of this research indicate that partially the variables of company growth and profitability have a significant effect on earnings management. Meanwhile, the education level of the board of directors and company age have no effect on earnings management. From this research, the coefficient of determination was also obtained (R2) with value 0.443639 means that it is as big as 44.36% disclosure is explained by the variables of board of directors' education level, company growth, profitability, and company age. Meanwhile, 55.64% is explained by other variables outside the model.